Development of a web-based community management information system - Beigzadeh, S. (IEEE Explorer, 2011)
This paper presents the development of a web-based system customized to serve the need of a community, named Taman Keramat Permai (TKP) in Malaysia. The system is designed to replace a paper-based process that gradually become unmanageable due to the increasing large volume of data. Features of the new system include online recording of forms, database query functions, electronic authorization, update, manage and monitor the progress data and activities included in TKP. We describe the design principles and introduce a functional component diagram for the system. The system is implemented on Windows platform using opensource software such as PHP4, MySQL, and Apache. Performance of the developed system is assessed practically and an efficient, and user friendly operation is demonstrated.